PENGARUHORIENTASI DANFRAKSI VOLUME SERAT DAUN NANAS (ANANAS COMOSUS)TERHADAP KEKUATAN TARIK KOMPOSIT POLYESTERTAK JENUH(UP) - Paryanto Dwi Setyawan; Nasmi Herlina Sari; Dewa Gede Pertama Putra (Universitas Mataram, 2012)
Composite manufacturing is done by hand lay-up method with a fiber volume fraction 10%, 20%, 30%, and 40% with unidirectional and random short fiber orientation of pineapple leaves. Specimen testing is performed with a standard tensile strength test ASTM D3039. As a results is known that the tensile strength of composites increased with increasing fiber volume fraction for unidirectional fiber orientation, but rather to the random orientation of short fibers. Meanwhile, the composite tensile strain increases withincreasingfibervolume fractionfor both theorientation of thefibersof pineappleleaves.